Thrombin Generation Assay and Hemostatic Profile for Elucidating Hypercoagulability in Endogenous Canine Hyperadrenocorticism - Vargas-Mora, Silvia E. [UNESP]; Romão, Felipe G. [UNESP]; dos Santos, Bruna; Carvalho, Maria das Graças; Duarte, Rita C.F.; De Marco Bernardes, Viviani; Lopes, Priscila A.; Takahira, Regina K. [UNESP] (Elsevier, 2021)
Canine hyperadrenocorticism is a common endocrine disorder caused by chronic secretion of glucocorticoid, often associated with hypercoagulability and secondary thrombosis. The thrombin generation assay (TGA) evaluates hemostasis globally by measuring endogenous thrombin potential. We aimed to determine whether TGA is suitable for assessing hypercoagulability in dogs with endogenous hyperadrenocorticism (HAC), and to correlate TGA with coagulation markers including fibrinogen, antithrombin (AT), D-dimer, prothrombin time (PT) and activated partial thromboplastin time (aPTT), and with routine laboratory tests for elucidating prothrombotic mechanisms and evaluating their utility as hypercoagulability screening tests. Thrombin generation performed with high activator concentration showed significantly higher endogenous thrombin potential (ETP) (P = .0239) and peak thrombin (P = .0281) in Cushing patients. Fibrinogen (P = <.0001) and AT (P = .0444) activities were significantly higher in the HAC group, while those of PT (P = .0046) and aPTT (P = .0002) were lower. Basal cortisol levels correlated positively with fibrinogen (r = 0.4503; P = .0355) and negatively with AT activity (r = -0.4580; P = .0280). Fibrinogen and hematocrit values were inversely correlated (r = -0.4853; P = .0076). Our study confirmed the presence of higher thrombin generation in dogs with HAC. However, TGA performed with lower activator concentrations was unsuitable for detecting hypercoagulability. Higher AT and fibrinogen levels and lower aPTT activity were identified in dogs with HAC relative to controls suggesting a potential role for the combined use of these assays when assessing hypercoagulability in canine hyperadrenocorticism.
Keywords: coagulation; cushing's syndrome; hypercortisolism; thrombosis